Water quality analysis and model simulation for the second largest polluted lake in Egypt - seifSeif, Diaa; Nasr, Mahmoud; R. Soliman, Mohamed; Moustafa, Medhat; Elbarki, Walid (International Journal of Engineering and Technology, 2018)
This study investigated the spatial variation in the water quality parameters of Burullus Lake using multivariate analysis and MIKE21 model. The lake was classified into zone-1 at north-east (Z1), zone-2 at south-east (Z2), zone-3 at north-middle (Z3), zone-4 at south-middle (Z4), zone-5 at north-west (Z5), zone-6 at south-west (Z6), and zone-7 at west (Z7). The obtained parameters were temperature 21.5Â±5.0 ÂºC, pH 8.2Â±0.6, dissolved oxygen (DO) 5.9Â±1.0 mg/L, biological oxygen demand (BOD) 23.9Â±5.7 mg/L, NH3-N 2.5Â±0.3 mg/L, NO2-N 1.9Â±0.3 mg/L, NO3-N 1.2Â±0.3 mg/L, PO4-P 1.9Â±0.3 mg/L, SiO4 3.2Â±0.1 mg/L, Chlorophyll-a (Chl-a) 88.2Â±10.8 Âµg/L, and salinity 3.2Â±1.0 g/L. Principal component analysis showed that agricultural drainage water was the key factor influencing the water quality characteristics of Burullus Lake. Water quality index (WQI) varied between â€œBadâ€ to â€œMediumâ€, suggesting that the lake wasnâ€™t suitable for irrigation and fish growth; however, it was appropriate for some aquatic life. A MIKE21 model was developed to provide a recommendation scenario that could be used to enhance the water quality of Burullus Lake. By improving the water quality of precise drains (namely drains 7 and 8), the WQI at Z4 and Z6 modified from â€œBadâ€ to â€œMediumâ€. The period required to achieve this self-purification was 5 months.Â Â